Chemical metabolome assay by high‐resolution Orbitrap mass spectrometry and assessment of associated antitumoral activity of Actinocephalus divaricatus. (15th January 2018) - Zanatta, Ana C.; Mari, Angela; Masullo, Milena; Zeppone Carlos, Iracilda; Vilegas, Wagner; Piacente, Sonia; Campaner dos Santos, Lourdes
Abstract : Rationale: Actinocephalus divaricatus (Eriocaulaceae) is an important source of income for rural communities as it is sold as an ornamental plant. To date, no investigation has been conducted concerning the chemical composition and biological studies of the aerial parts of A. divaricatus . Methods: The methanolic extract of the aerial parts of this species was chemically characterized. We applied an analytical dereplication approach based on Liquid Chromatography coupled to High‐Resolution Orbitrap Mass Spectrometry in order to develop, identify and define rapidly the metabolite fingerprint of the aerial parts of A. divaricatus. Biological in vitro antitumor tests were undertaken using breast and lung cell lines of mice and humans. Results: High‐Resolution Mass Spectrometry (HRMS) allowed the fast determination of 30 compounds, which comprised three different classes of compounds: naphthopyranones, flavonoids and saponins. Chromatographic fractionation of the crude methanolic extract validated these results, since it led to the isolation of compounds belonging to the aforementioned classes of compounds, including new acyl glycosylated flavonoids (6‐hydroxy‐7‐methoxyquercetin‐3‐ O ‐(2"‐ O ‐acetyl)‐ β ‐D‐glucopyranoside and 6‐hydroxy‐7‐methoxyquercetin‐3‐ O ‐(6"‐ O ‐acetyl)‐ β ‐D‐glucopyranoside), which were fully characterized by Nuclear Magnetic Resonance and Mass Spectrometry experiments, and a known triterpenic saponin (3‐ O ‐ β ‐D‐glucuronopyranosyl‐30‐norolean‐12, 20(29)‐dien‐28‐ O ‐ β ‐D‐glucopyranosyl ester). Biological assays indicated that the methanolic extract of the capitula exhibited the best in vitro cytotoxicity against MCF7 cells (human breast cancer). Conclusions: The HRMS technique enabled us to identify several classes of compounds. In addition, saponins were identified for the first time in plants belonging to the Eriocaulaceae family. Thus, the essential contribution of this work lies in the new elements it brings to the taxonomic discussion which the Actinocephalus genus as a distinct genus of the Paepalanthus. The results obtained show that the methanolic extract of the capitula could be a promising source of bioactive fractions and/or compounds that may contribute towards breast cancer treatment.